2007
DOI: 10.1096/fj.06-6558com
|View full text |Cite
|
Sign up to set email alerts
|

SDF‐1 expression by mesenchymal stem cells results in trophic support of cardiac myocytes after myocardial infarction

Abstract: Stem cell transplantation at the time of acute myocardial infarction (AMI) improves cardiac function. Whether the improved cardiac function results from regeneration of cardiac myocytes, modulation of remodeling, or preservation of injured tissue through paracrine mechanisms is actively debated. Because no specific stem cell population has been shown to be optimal, we investigated whether the benefit of stem cell transplantation could be attributed to a trophic effect on injured myocardium. Mesenchymal stem ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
336
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 412 publications
(359 citation statements)
references
References 37 publications
17
336
0
6
Order By: Relevance
“…This conclusion is supported by our data that inhibition of CXCR4 by miRNA-CXCR4 significantly reduced homing of transplanted MSCs to the ischemic myocardium resulting in limited myocardial regeneration and angiogenesis. Our data support recent reports that the SDF-1α/CXCR4 interaction is important for MSCs migration to the infarcted myocardium and angiogenesis [6,38]. However, the approach in this study used the delivery of CXCR4 over-expressing MSCs rather than delivery of SDF-1α expressing MSCs.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This conclusion is supported by our data that inhibition of CXCR4 by miRNA-CXCR4 significantly reduced homing of transplanted MSCs to the ischemic myocardium resulting in limited myocardial regeneration and angiogenesis. Our data support recent reports that the SDF-1α/CXCR4 interaction is important for MSCs migration to the infarcted myocardium and angiogenesis [6,38]. However, the approach in this study used the delivery of CXCR4 over-expressing MSCs rather than delivery of SDF-1α expressing MSCs.…”
Section: Discussionsupporting
confidence: 90%
“…Besides their migratory role, these CXCR4 positive MSCs participated in neovascularization and differentiated into new myocytes. In addition, MSCs secrete or express SDF-1α [34,35] and its interaction with CXCR4 increases survival of progenitor cells [6]. SDF-1α could serve as an adhesive molecule by binding CXCR4-expressing cells to the vessel wall [36], which is consistent with our study that a high degree of CXCR4 expression is observed in the vascular endothelial cells.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Transplantation of cells engineered to express SDF-1 into the peri-infarct zone following coronary occlusion in the rat resulted in attenuated adverse remodeling [116]. The beneficial effects of SDF-1 may be due to therapeutic stem cell homing into the injured myocardium resulting in neovascularization and enhanced preservation of cardiomyocytes [118]. Local delivery of SDF-1 in the infarct may exert beneficial actions by augmenting vasculogenesis and by protecting ischemic cardiomyocytes from apoptosis without inducing cardiomyocyte regeneration.…”
Section: Chemokines In Healing Infarctionmentioning
confidence: 99%